2021
DOI: 10.21037/tlcr-21-15
|View full text |Cite
|
Sign up to set email alerts
|

First-line immunotherapy in non-small cell lung cancer patients with poor performance status: a systematic review and meta-analysis

Abstract: Background: Immune checkpoint inhibitors (ICIs) have become the standard of care for the first-line treatment of advanced non-small cell lung cancer patients (NSCLC), either as single agents or combined with chemotherapy. The evidence sustaining their role for poor performance status (ECOG PS ≥2) patients is limited. Methods:We search PubMed and the proceedings of international oncology meetings to perform a systematic review to assess the outcomes poor PS NSCLC patients who received ICIs as first-line treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 69 publications
1
19
0
Order By: Relevance
“…A poor PS remains a strong prognostic factor for ICIs, as described in prospective and retrospective studies. Recently, Facchinetti et al reported a systematic review and metaanalysis of the clinical usefulness of first-line immunotherapy in NSCLC patients with a poor PS [16]. In their systematic review, 41 studies were chosen, and 1030 of 5357 (19%) of the patients in 30 studies on first-line pembrolizumab presented with an ECOG PS of 2-4 at pembrolizumab initiation.…”
Section: Retrospective Analysis Of First-line Pembrolizumab In Pd-l1 ≥ 50% Nsclc With a Poor Psmentioning
confidence: 99%
“…A poor PS remains a strong prognostic factor for ICIs, as described in prospective and retrospective studies. Recently, Facchinetti et al reported a systematic review and metaanalysis of the clinical usefulness of first-line immunotherapy in NSCLC patients with a poor PS [16]. In their systematic review, 41 studies were chosen, and 1030 of 5357 (19%) of the patients in 30 studies on first-line pembrolizumab presented with an ECOG PS of 2-4 at pembrolizumab initiation.…”
Section: Retrospective Analysis Of First-line Pembrolizumab In Pd-l1 ≥ 50% Nsclc With a Poor Psmentioning
confidence: 99%
“…However, there is a lack of real-world data from prospective observational studies examining first-line pembrolizumab monotherapy in patients with advanced NSCLC who are unfit for clinical trials, such as those with poor PS and elderly patients. Facchinetti et al reported in their meta-analysis of first-line immunotherapy for NSCLC patients with poor PS that prospective evidence supporting the role of immunotherapy in this population is limited, and clinical efforts are needed to improve prognosis, including the definition and factors contributing to poor PS and the development of dedicated treatment strategies (13).…”
Section: Introductionmentioning
confidence: 99%
“…By a recent meta-analysis, first-line ICIs in NSCLC patients with poor PS were described to be associated with worse outcome [ 11 , 12 ]. As our study indicated that low numbers of stromal CD4 TILs was closely related to poor PS, the degree of CD4 + T cell infiltration into the stroma may affect the patient’s general condition.…”
Section: Discussionmentioning
confidence: 99%